PENGUNGKAPAN PRIBADI REMAJA KELUARGA BROKEN HOME - Melita, Yerah; Elisabeth, Melva (Jurnal Insani, 2024)
A family is a group of individuals living together, bound by blood relations and marital ties. Withinfamily life, misunderstandings, differing opinions, and contrasting perspectives often arise, leading todisputes or conflicts among family members. In some cases, these disagreements escalate and, if notmanaged effectively, result in separation or divorce. Such familial conflicts can cause fractures or criseswithin the family structure, ultimately leading to the dissolution of the household, commonly referred toas a "broken home." A broken home can have significant negative impacts, particularly on children,with adolescents being especially vulnerable due to the stigma associated with the term, which oftenlabels the family as dysfunctional. When a separation or divorce occurs, adolescents frequentlyexperience feelings of shame, choosing to conceal their family situation from others. As victims of suchcircumstances, they tend to withhold details about their personal lives, seeking solace in trusted friendswith whom they can share their experiences privately. This study explores the private self-disclosure ofadolescents from broken home using the Communication Privacy Management Theory. A qualitativeresearch method was employed, utilizing purposive sampling to select three informants. Data collectiontechniques included observation, interviews, and documentation. The findings reveal that adolescentsfrom broken homes disclose personal information consciously and cautiously, carefully selecting friendsto confide in. However, they also choose to withholdor keep highly personal information private, optingnot to share it with anyone.